x -y = 1
5x + 3y = 45
Solve the first equation for x: x = y + 1
Substitute x in the second with y + 1
5x + 3y = 45
5(y + 1) + 3y = 45
5y + 5 + 3y = 45
8y + 5 = 45
8y = 40
y = 5
Substitute 5 for y in x = y + 1
x = y + 1
x = 5 + 1
x = 6
Answer: (6, 5)
Answer:
0
Step-by-step explanation:
x and x are same terms.
Answer:
Step-by-step explanation:
a) The objective of the study is test the claim that the average gain in the green fees , lessons or equipment expenditure for participating golf facilities is less than $2,100 under the claim the null and alternative hypothesis are,
H₀ : μ = $2,100
H₀ : μ < $2,100
B) Suppose you selects α = 0.01
The probability that the null hypothesis is rejected when the average gain is $2,100 is 0.01
C) For α = 0.01
specify the rejection region of a large sample test
At the given level of significance 0.01 and the test is left-tailed then rejection level of a large-sample = < - 1.28
Answers: 11-20
Step-by-step explanation: Step 1. Flip the equation Step 2. Add the number to both sides Step 3. Divide both sides by the number to get your answer.
1. v=10 2. m=7 3. r=-9 4. k=9 5. r=0 6. x=10 7. x=6 8. 9=3 9. m=-10 10. n=-10
11.p=0
12.x=10
13.b=4
14.n=0
15.p=2
16.x=8
17.m=8
18.x=3
19.n=-1
20.n=9